Mechanical vibration practice and noise control - Ramamurti, V. ([S.l.] : Alpha Science International Ltd, 2008)
Mechanical Vibration Practice and Noise Control stresses the importance of physical parameters of significance associated with vibration and industrial noise and lateral and torsional critical speeds of industrial rotors. Design features of metallic and non metallic isolators, machine foundations, transducers and exciters enhance the value of the book. Also included are the International Standards on noise and vibration. Seventeen case studies on industrial problems solved for process industries and engine diagnostics are very useful to a practising engineer. Presentation of 3-D beam finite element method and two plane field balancing along with source codes in C and FORTRAN languages and over 100 worked out examples on industrial problems make the book versatile. Hints to exercises will be a priceless possession for students, teachers and professional Engineers.